PENGARUH PERTUMBUHAN EKONOMI, INVESTASI, TINGKAT INFLASI, DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAMBI - Mira Hastin; Ferry Siswadhi (LPPM - STIE SAKTI ALAM KERINCI, 2021)
This study aims to determine how the effect of economic growth, investment, inflation rate, and unemployment to the level of poverty in Jambi Province in 2010-2019. The method used in this research is the method of multiple linear regression. This type of research is quantitative descriptive with secondary data from the Central Statistics Agency of Jambi Province. The study results by testing the partial regression coefficient showed that investment has a significant influence on poverty levels in Jambi Province. While, economic growth, inflation rate, unemployment had no effect on poverty level in Jambi Province. The effect of investment on poverty level is negative, which means that if investment increases then poverty level will decrease. Furthermore, simultaneous results indicate that together with economic growth, investment, inflation rate, unemployment had no effect on poverty level in Jambi Province. This implies that economic growth, investment, inflation, and unemployment in Jambi Province can not reduce poverty. Based on the results of the study, it is suggested that Investment should be in favor of the interests. Although the inflation rate does not affect the level of poverty but the government must keep control and maintain the inflation rate. Economic growth should still be spurred by growth. The unemployment rate should be lowered each period